2016
DOI: 10.1016/j.parkreldis.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease, visual hallucinations and apomorphine: A review of the available evidence

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 94 publications
(146 reference statements)
2
23
0
8
Order By: Relevance
“…The chemical structure of apomorphine includes a piperidine moiety and, unlike other dopamine agonists, this drug exerts intrinsic antagonist effects at the 5-HT 2A receptor as well as agonist affects at both D1-like and D2-like receptors 148 . This unique profile might account for case report and open-label study evidence that apomorphine does not exacerbate psychosis symptoms and, in some studies, may ameliorate these symptoms 149 or improve visual contrast sensitivity 150 .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical structure of apomorphine includes a piperidine moiety and, unlike other dopamine agonists, this drug exerts intrinsic antagonist effects at the 5-HT 2A receptor as well as agonist affects at both D1-like and D2-like receptors 148 . This unique profile might account for case report and open-label study evidence that apomorphine does not exacerbate psychosis symptoms and, in some studies, may ameliorate these symptoms 149 or improve visual contrast sensitivity 150 .…”
Section: Treatmentmentioning
confidence: 99%
“…The effect size for apomorphine (0.32) was larger than for intrajejunal levodopa (0.29), although the difference was not significant 152 . Apomophine might have a place in the treatment of PD psychosis; however, a better evidence base is needed to guide future recommendations 148,152,153 .…”
Section: Treatmentmentioning
confidence: 99%
“…Similar data were found for users of dopamine agonists in a meta-analysis and review studies. 41,42 Based in the context of drug-induced visual hallucinations in Parkinson's disease patients, magnetic resonance imaging studies have suggested the importance of dopamine in the development of visual hallucations, showing that PD patients frequently display progressive atrophy in the paralimbic, limbic, and neocortical areas, as well as in cerebral areas in which dopamine is the main neurotransmitter. 43 In contrast, we observed a protective effect in the occurrence of visual hallucinations in users of entacapone and amantadine, after the analyses of the multiple Poisson regression.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the hallucinogenic potency of 5-HT 2A receptor agonists, such as psilocybin, mescaline and Lysergic  acid  diethylamide (LSD). Additionally, apomorphine has been suggested to treat visual hallucinations as a 5-HT 2A receptor antagonist in Parkinson’s disease (PD) 4. The role of the 5-HT 2A receptor in visual hallucinations in PD is supported by positron emission tomography (PET) studies comparing patients with PD with and without visual hallucinations, demonstrating an increased 5-HT 2A binding in the prefrontal and visual processing areas of the hallucinating patients 4 5…”
Section: Discussionmentioning
confidence: 99%